Laser structuring of crystalline silicon thin-film solar cells on opaque foreign substrates - Kunz, T.; Gazuz, V.; Hessmann, M. T.; Gawehns, N.; Burkert, I.; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2011)
Crystalline silicon thin-film solar cells were fabricated on graphite substrates. A laser ablation process was developed for edge isolation of the thin-film cells. The shunt resistance was comparable to otherwise identical cells isolated by plasma etching, while the reproducibility of the laser isolation process was higher. The solar cells were characterized by currentvoltage and light beam induced current measurements (LBiC). No interference was detected along the ablated edges. Spatial variations of the minority carrier lifetime are attributed to the grain structure of the seeding layer obtained by the zone melting recrystallization (ZMR). © 2011 Elsevier B.V.
Keywords: Crystalline thin-film silicon; Edge isolation; Graphite substrate; Laser processing